The Influence of Management Practices on Employee Commitment and Food Safety Performance in Food Manufacturing Firms - TAHA, SADI MOHAMMAD SADI (2018)
Traditional training, food testing, inspections, and adopting various food safety management systems are commonly used solutions to improve food manufacturing safety. Despite the implementation of these interventions, food borne illnesses, food product recalls, and food safety violations persist. With the purpose of improving food safety practices and performance, it is argued that food manufacturing firms focus on the behavioural issues of their food handlers. Previous studies have focussed on behaviour and researchers have used different theories to investigate how knowledge and training may affect food handlers’ behaviour. The theories used include social norms theory, reasoned action theory, and the theory of planned behaviour.The existing literature emphasises the need for researchers to investigate the organisational factors that could influence the behavioural intentions of food handlers. However, no studies have been conducted that have investigated the impact of different management practices on food handlers’ behaviour with regard to the implementation of safe food procedures and organisational food safety performance. Thus, this study expands the literature and uses commitment theory to assess how a range of management practices influences food handlers’ commitment and organisational food safety performance. The objectives of this research are to critically investigate the impacts of several management practices – specifically, management support, communication, training, and employee involvement – on food handlers’ commitment towards food safety performance in food manufacturing firms based in the United Arab Emirates (UAE). The study examines the mediation effect of the food handlers’ commitment on the relationship between the management practices and the food safety performance of the firms. The sample comprised 189 food manufacturing firms operating in the Emirate of Dubai.This research adopted a positivist philosophy, and a quantitative deductive approach. Two focus groups were conducted to support the literature analysis and to gain more information from the participants to support the research aims, which validated the draft survey instrument that had been based on the literature. Data were collected by using a self-administered hard copy survey questionnaire that was completed by five food handlers in each of the 189 firms. The data analysis was accomplished using the Statistical Package for the Social Sciences (SPSS) and structural equation modelling (AMOS) by means of multiple regression, path and mediation analysis. It was found that all of the studied management practices have a direct significant positive impact on the food handlers’ commitment to implementing safe food procedures. Furthermore, the food handlers’ commitment has a significant positive impact on organisational food safety performance.The results also indicate that the food handlers’ commitment fully mediates the relationship between the training and food safety performance of food manufacturing firms. Similarly, the food handlers’ commitment fully mediates the relationship between employee involvement and the food safety performance of food manufacturing firms. The food handlers’ commitment was found to partially mediate the relationship between organisational management support and the food safety performance, and similarly the food handlers’ commitment was found to partially mediate the relationship between communication and the food safety performance. These results indicate that food handlers’ commitment is a mediator in the relationship between all of the studied management practices and the food safety performance of food manufacturing firms. Based on the mediation results, the association between employee involvement and training was examined and found significantly associated. This suggests that employee involvement can be an important factor in boosting training effectiveness, such as the food handlers’ skills levels and their work performance when they are involved in decision making, or their problem solving in daily work activities. This indicates that learning is not a product with an identifiable outcome endorsed with a completion or attendance certificate. Rather, it is a process in which learners enhance their work performance when they are involved and able to translate the knowledge obtained through training into practice during daily work activities. To the knowledge of the researcher, this is the first empirical study that uses commitment theory to investigate the antecedents of food handlers’ commitment to implement safe food procedures, and the influence of management practices and food handlers’ commitment on organisational food safety performance. Most of the previous studies have used behavioural theories focusing on explaining the behaviour itself, which considered the normative influences without accounting for the environmental or economic factors that may affect an employee’s intention to perform a particular behaviour.This study contributes to knowledge by presenting a conceptual model, which builds upon and improves the existing models of food safety management, by introducing commitment theory to the present behavioural theories. It succeeded in explaining the management practices that influence food handlers’ commitment to implementing safe food procedures, and how both these practices and the food handlers’ commitment may impact upon organisational food safety performance. It is concluded that food handlers with strong commitment are more likely to implement safe food procedures, thus contributing to the organisation’s food safety performance. The findings suggest that the managers of food manufacturing firms should analyse the impacts of their management practices and create policies that motivate and improve employee commitment and performance. Further implications of the results and future research directions are also presented.